2021
DOI: 10.1002/eji.202049006
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory receptor CD300a is essential for neutrophil‐mediated clearance of urinary tract infection in mice

Abstract: Neutrophils play a crucial role in immune defense against and clearance of uropathogenic Escherichia coli (UPEC)-mediated urinary tract infection, the most common bacterial infection in healthy humans. CD300a is an inhibitory receptor that binds phosphatidylserine and phosphatidylethanolamine, presented on the membranes of apoptotic cells. CD300a binding to phosphatidylserine and phosphatidylethanolamine, also known as the "eat me" signal, mediates immune tolerance to dying cells. Here, we demonstrate for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…This is not surprising, since also in a previous report no differences were found between WT and CD300a −/− ability to phagocytize apoptotic cells in C57BL mice [14]. However, in previous reports, CD300a −/− mice presented with impaired phagocytosis of fluorescent beads by neutrophils [18] and defective efferocytosis of apoptotic neutrophils by peritoneal MΦ [19]. It is possible that CD300a differentially influences phagocytosis and efferocytosis on different cells according to the target employed (beads or apoptotic cells).…”
Section: Discussionmentioning
confidence: 56%
“…This is not surprising, since also in a previous report no differences were found between WT and CD300a −/− ability to phagocytize apoptotic cells in C57BL mice [14]. However, in previous reports, CD300a −/− mice presented with impaired phagocytosis of fluorescent beads by neutrophils [18] and defective efferocytosis of apoptotic neutrophils by peritoneal MΦ [19]. It is possible that CD300a differentially influences phagocytosis and efferocytosis on different cells according to the target employed (beads or apoptotic cells).…”
Section: Discussionmentioning
confidence: 56%
“…Under the basal epithelium, the resident mast cells, NK cells, Ly6C − macrophages, and 𝛾𝛿T cells function as sentinels to sense UPEC infection, and neutrophils and Ly6C + macrophages are further recruited into the bladder to eliminate the bacteria. [17,23,[31][32][33][34][35] ILCs play a critical role in the host defense against pathogens in other barrier tissues, such as the gut, lung, and skin, [12,13] and it has been reported that CD4 + ILC3 levels are increased in the bladder of UPEC-infected mice. [36] However, whether bladder-resident ILCs respond to UPEC infection, and whether ILC3s play a crucial role in defending against UPEC during an infection, remain to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, a major role is played by molecules that regulate the cellular innate immune signalling/response, in an event of phagocytic activity, thus preventing an excessive pro-inflammatory cytokine release that could compromise the BTB. We have recently shown, for the first time in Sertoli cells, a functional Nlrp3 inflammasome able to elicit pro-inflammatory cytokine response and cell death, upon stimulation of the NF-κB converging NOD1 and TLR4, in the presence of danger signal as ATP that could serve as a cornerstone for BTB disruption and potential infertility upon proper pathogenic stimulation [ 8 ]. We have also found that NOD1 challenge strongly upregulated the CD300a receptor (unpublished ), which recognizes phosphatidylserine and phosphatidylethanolamine presented on apoptotic cell membranes [ 8 ].…”
mentioning
confidence: 99%
“…We have recently shown, for the first time in Sertoli cells, a functional Nlrp3 inflammasome able to elicit pro-inflammatory cytokine response and cell death, upon stimulation of the NF-κB converging NOD1 and TLR4, in the presence of danger signal as ATP that could serve as a cornerstone for BTB disruption and potential infertility upon proper pathogenic stimulation [ 8 ]. We have also found that NOD1 challenge strongly upregulated the CD300a receptor (unpublished ), which recognizes phosphatidylserine and phosphatidylethanolamine presented on apoptotic cell membranes [ 8 ]. CD300a is a member of the CD300 type I trans-membrane glycoproteins, signalling via its ITIM motif and being regulated by internalization [ 9,10 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation